Analisis Kinerja Keuangan Daerah Tahun Anggaran 2011 – 2015 Di Kabupaten Sumedang Provinsi Jawa Barat - Hafifurrahman Hasan (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2017)
AbstractLocal financial performance is one measure to see the ability of local in the running local autonomy, especially in implementing fiscal decentralization. Seeing this, the authors are interested in doing research with the title